Pogledi mentorjev na praktično pedagoško usposabljanje študentov pedagogike - Rus, Danijela (Revija za elementarno izobraževanje, 2016)
Mentors’ Views on Practical Educational Training of Students of Pedagogy. The article begins by introducing the importance of practical pedagogical training of students, whereas the focus is on mandatory practical pedagogical training of students at two programmes of the Faculty of Arts, University of Maribor: the undergraduate doublemajor programme Pedagogy and the postgraduate double-major teacher programme Pedagogy. The first part describes the importance of mentoring and mentor´s role in the process of practical pedagogical training. The role of the school counsellor in an educational institution is also described. Research results are presented in the second part of the article. Here, the school mentors (school counsellors) were interviewed about school counsellor competencies, about the development of different counsellor competencies during the practical pedagogical training of students of Pedagogy and with the help of their mentor and about the overall opinion about the entire course of practical pedagogical training.